Degrees of Affinity : - Wang, Zuoliang. (Springer Berlin Heidelberg, 2015)
This book combines two collections of essays written by the late professor Zuoliang Wang, works that explore the affinity between literatures and peoples, with special attention given to that between Chinese literature and western literature in the 20th century, and which underscore the role of translation therein. Both collections have been previously published in book form: Degrees of Affinity—Studies in Comparative Literature (1985) and A Sense of Beginning—Studies in Literature and Translation (1991). As a prominent literary critic, literary historian, translator and 20th-century Chinese poet, Wang has played a unique part in English education in China. His research interests range widely, from English literature through comparative literature to translation and cultural studies, fields in which he has made outstanding accomplishments. Wang pioneered the concept of “affinity” in talking about interactions between literatures and peoples, which has since won great acclaim from both critics and common readers at home and abroad. As he points out, “momentous changes often occur when a foreign literature satisfies a sore need of an indigenous literature, thus developing a strong affinity...” And translation can fulfill a crucial role in bringing about affinity between literatures and peoples. According to Professor Wang, “Nothing is more crucial in cultural contacts, not to say cultural interactions, than translation, particularly in a country that for long periods closed its doors to the outside world, like China.”.
10.1007/978-3-662-45475-6
Keywords: Comparative literature.; Comparative Literature.